Diabetes care and transgender health: Clinical pearls - Sanjay Kalra,; Ashok Kumar,; Rakesh Sahay, (Journal of the Pakistan Medical Association, 2023)
Diabetes and other cardiometabolic diseases occur across the world, and do not discriminate between populations. This communication reviews the epidemiology and etiology of diabetes in the transgender population, and highlights clinical issues that must be kept in mind while evaluating and managing the condition. It adds value to existing literature by equipping health care professionals with specific skills designed to enhance diabetes care delivery, and results, in transgender individuals. Keywords: diabetes, genital tract infections, insulin resistance, metabolic syndrome, SGLT2i, transgender